Review Paper for Nutrients in food - Hassan, Yasemin Ahmed; Ercoşkun, Hüdayi (Newinera Publisher, 2023)
The diet exerts a substantial influence on chronic illnesses and overall well-being. Addressing food-related behaviors will enable individuals to manage these conditions effectively. Enhancing health by making changes to one's diet through modification and fortification, introducing novel food options, and including essential nutrients. Enriched and utilitarian food products, supplements, and health-promoting substances Fortified meals and functional foods are designed to augment the nutritional requirements of individuals. Some meals, like morning cereals, are regularly enriched with vitamins and minerals, and there is a growing variety of foods that are enhanced with specific functions and claimed to provide health benefits. Nutraceuticals, also known as nutriceuticals, are naturally occurring bioactive chemicals that possess qualities that promote health or prevent diseases. The study investigated the correlation between nutrition and its influence on human well-being. It provided evidence that diet plays a significant role as an environmental component in the development of many chronic illnesses. Quantifying the precise magnitude of this impact is challenging, however, there has been a notable 35% decrease in the occurrence of Cancer among different age groups in the United States. The states have been proposed to be attainable using